Vulvar Pigmented Growth: A Psychological Concern? - Pathak, Deeptara; Agrawal, Sudha; Dhali, Tapan (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i2.5079 NJOG 2010 Nov-Dec; 5(2): 46-47